Clinical, neuroimaging, and metabolic footprint of the neurodevelopmental disorder caused by monoallelic HK1 variants - Wortmann, Saskia B.; Feichtinger, Rene G.; Abela, Lucia; van Gemert, Loes A.; Aubart, Mélodie; Dufeu-Berat, Claire-Marine; Boddaert, Nathalie; de Coo, Rene; Stühn, Lara; Hebbink, Jasmijn; Heinritz, Wolfram; Hildebrandt, Julia; et al. (Neurology. Genetics, 2024)
Background and Objectives - Hexokinase 1 (encoded by HK1) catalyzes the first step of glycolysis, the adenosine triphosphate-dependent phosphorylation of glucose to glucose-6-phosphate. Monoallelic HK1 variants causing a neurodevelopmental disorder (NDD) have been reported in 12 individuals. - Methods - We investigated clinical phenotypes, brain MRIs, and the CSF of 15 previously unpublished individuals with monoallelic HK1 variants and an NDD phenotype. - Results - All individuals had recurrent variants likely causing gain-of-function, representing mutational hot spots. Eight individuals (c.1370C>T) had a developmental and epileptic encephalopathy with infantile onset and virtually no development. Of the other 7 individuals (n = 6: c.1334C>T; n = 1: c.1240G>A), 3 adults showed a biphasic course of disease with a mild static encephalopathy since early childhood and an unanticipated progressive deterioration with, e.g., movement disorder, psychiatric disease, and stroke-like episodes, epilepsy, starting in adulthood. Individuals who clinically presented in the first months of life had (near)-normal initial neuroimaging and severe cerebral atrophy during follow-up. In older children and adults, we noted progressive involvement of basal ganglia including Leigh-like MRI patterns and cerebellar atrophy, with remarkable intraindividual variability. The CSF glucose and the CSF/blood glucose ratio were below the 5th percentile of normal in almost all CSF samples, while blood glucose was unremarkable. This biomarker profile resembles glucose transporter type 1 deficiency syndrome; however, in HK1-related NDD, CSF lactate was significantly increased in all patients resulting in a substantially different biomarker profile. - Discussion - Genotype-phenotype correlations appear to exist for HK1 variants and can aid in counseling. A CSF biomarker profile with low glucose, low CSF/blood glucose, and high CSF lactate may point toward monoallelic HK1 variants causing an NDD. This can help in variant interpretation and may aid in understanding the pathomechanism. We hypothesize that progressive intoxication and/or ongoing energy deficiency lead to the clinical phenotypes and progressive neuroimaging findings.